Translator Style: An Analysis on Two Indonesian Translations of “A Scandal in Bohemia” - Suwarni Wijaya Halim (Soegijapranata Catholic University, 2020)
Abstract: For many years, it is believed that a good translator should be invisible in conducting his or her work. The more transparent and invisible the translator is, the better the quality of translation becomes. However, many experts argued that it is actually impossible for the translators to translate without leaving their thumbprints behind. Thus, the notion of translator style appeared. Studying and exploring the topic of translator style would provide more corroborative support on the view that translators are not merely a mirror of the original author; in fact, they are creative individuals with distinct linguistic characteristics and behaviors, and that translation is not inferior to writing. The objective of this study is to analyze the style of two Indonesian translators of Sir Arthur Conan Doyle’s “A Scandal in Bohemia.” Moreover, this research also aims to enrich the literature of translator style in the Indonesian context since there are only a few studies about this particular topic in the Indonesian context. This research is qualitative in nature and utilized both corpus-assisted methodology and manual text analysis to gain the data. The findings show that the two Indonesian translators had fundamental differences in their translation. Translator A’s style in translating is more oriented to target text and target readers whereas Translators B are more inclined to adhere to the style of the original author and the source text.Key words: translator style, literary work, short storyAbstrak: Selama bertahun-tahun, banyak pihak yang meyakini bahwa seorang penerjemah yang baik seharusnya transparan dalam melakukan pekerjaannya. Semakin transparan penerjemahnya, semakin baik kualitas terjemahannya. Namun, banyak ahli berpendapat bahwa sebenarnya tidak mungkin penerjemah menerjemahkan tanpa meninggalkan jejak. Oleh karena itu, gagasan mengenai gaya penerjemah muncul. Mempelajari dan mengeksplorasi topik mengenai gaya penerjemah akan memberikan dukungan yang lebih kuat pada pandangan bahwa penerjemah bukan sekadar cermin dari penulis asli; pada kenyataannya, mereka adalah individu yang kreatif dengan karakteristik dan perilaku linguistik yang berbeda, dan kegiatan penerjemahan itu tidak kalah penting dengan kegiatan menulis. Tujuan dari penelitian ini adalah untuk menganalisis gaya dua penerjemah karya Sir Arthur Conan Doyle yang berjudul